Ad Fontes Digitales!?: Margins of Representation When Incorporating Medieval Sources into a German Digital History Textbook. Issue 2 (1st September 2020) - Willershausen, Andreas
Abstract: The publication of the first German-language digital history textbook, mBook: History for the Future ( mBook: Geschichte für die Zukunft, Cornelsen Verlag, 2016), drew much critical attention. In 2018, the mBook was awarded the prize for best textbook in the "society" category by the Georg Eckert Institute for its focus on improving learner competence. This article begins by assessing the mBook' s gradation feature (which allows for the linguistic gradation of sophisticated textual sources on several learning levels) and the textbook authors' aspiration to convey methodological competence and foster understanding of unfamiliar topics (Fremdverstehen), with the help of work on documents, and an understanding of historical times far removed from our own. It quantitatively and descriptively assesses textual documents in the chapters about the Middle Ages, while focusing on their textual preparation and digital implementation.